THE SEDIMENTOLOGY OF HYDROCARBON RESERVOIR ROCKS IN INDONESIA, A CASE STUDY FROM THE NORTH SUMATRA BASIN - G.K. Lott; Sundoro Sundoro (Scientific Contributions Oil and Gas, 1990)
The North Sumatra backarc basin has been an important hydrocarbon province for more than 100 yrs. High grade light oils and condensates have been produced from sandstone reservoirs in the deltaic Keutapang Formation and the shallow marine sandstones of the Baong Formation. The basin has a high geothermal gradient, which is in the order of 40-50 C/km (compared to 30/km in the North Sea or Gulf Coast areas) and is a result of its position close to the subducting margin of the Indian Ocean Plate.